2017
DOI: 10.14419/ijpr.v5i2.8042
|View full text |Cite
|
Sign up to set email alerts
|

A single hybrid parameter-based model for calibrating hargreaves-samani coefficient in Nigeria

Abstract: The present research was designed to locally calibrate Hargreaves-Samani computing model (HS) in twenty-one (21) locations with their corresponding coastal and interior regions in Nigeria employing a single hybrid parameter-based model to obtain the adjusted Hargreaves-Samani coefficient (AHC) for Nigerian environment. To achieve this purpose, meteorological parameters such as extraterrestrial solar radiation, maximum sunshine duration, minimum and maximum temperatures were employed as input parameters to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The H data measured in kwhm -2 day -1 were converted to MJm -2 day -1 using a factor of 3.6 [33] and was further converted to EM -1 using a converting factor of 4.56 [1]. The details of the study area are found in Nwokolo and Ogbulezie [31]. …”
Section: Acquisition Of Data and Study Areamentioning
confidence: 99%
“…The H data measured in kwhm -2 day -1 were converted to MJm -2 day -1 using a factor of 3.6 [33] and was further converted to EM -1 using a converting factor of 4.56 [1]. The details of the study area are found in Nwokolo and Ogbulezie [31]. …”
Section: Acquisition Of Data and Study Areamentioning
confidence: 99%
“…The GHI and DHI data measured in kwhm -2 day -1 were converted to MJm -2 day -1 using a factor of 3.6. The details of the study area are found in Nwokolo and Ogbulezie [19]. …”
Section: Acquisition Of Data and Study Areamentioning
confidence: 99%
“…It is therefore imperative to analyse DHI using GHI and clearness index obtained from NASA data. This will produce DHI data as a baseline for further scientific, environmental and atmospheric research without the substantial cost of the instrumentation network that would otherwise be needed [17][18][19]. The aim of this research paper is to develop an empirical model for estimating DHI in six tropical ecological zones in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, the global solar radiation models are classified according to the basis of their input parameters applied in correlating with the clearness index. The clearness index (kt) indicates the percentage depletion by the sky of the incoming solar radiation and therefore, gives both the level of availability of solar radiation and changes in the atmospheric condition in a given environment [11][12]. Mathematically, clearness index is the ratio of horizontal global solar radiation (often measured and collected from Nigeria Meteorological Station (NIMET), International Institute of Tropical Agriculture (IITA), National Aeronautics and Space Administration (NASA) atmospheric science data center by researchers in Nigeria) to the extraterrestrial solar radiation (Ho) on a daily or monthly basis as found in literature expressed as:…”
Section: Empirical Modelsmentioning
confidence: 99%
“…These assessments have involved direct measurement with meteorological measuring instrument such as Eppley pyranometer and satellite remote-sensing instrument such as Moderate-Resolutoin Imaging Spectroradiometer (MODIS) products, and meteosat-images etc. Due to cost implication, maintenance, expertise involved in ground measurement and satellite-derived data, especially in rural and developing locations in Nigeria, numerous estimation models employing empirical, artificial neutral network and other techniques were proposed in Nigeria by solar-energy researchers that can produce global solar radiation data without the substantial cost of the instrumental network that would otherwise be needed [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%